Chemical characterization and antioxidant potential of stevia rebaudiana bertoni essential oil obtained from subcritical carbon dioxide extraction - Mat Yusof, Muhammad Fahmi (2018)
Many aromatic and medicinal plants are available in Malaysia from which the essential oil (EO) can be extracted and used for multipurpose. The increasing number of cases of noncommunicable diseases (NCDs) such as diabetes, cancer, respiratory diseases, and cardiovascular diseases is becoming a growing concern, thus through the extraction of EO from Stevia rebaudiana, it can become an agent to cure these diseases. S. rebaudiana EO was extracted using subcritical carbon dioxide (SC-CO2) method for the first time and their chemical compounds were characterized by gas chromatography-mass spectrometry (GC-MS) and Fourier transform-infrared (FT-IR) spectroscopy. The highest productivity, yield of the extracted EO was found in the sample to an ethanol ratio of 1:0.5 with 5.6%, followed by the ratio of 1:1 with 3.6% and 1:1.5 with 2.4%. About 33 up to 50 compounds were identified in EO through GCMS method which representing 89.32%, 92.45%, and 81.42% of identified compound out of the total oil at different extraction ratio of 1:0.5, 1:1, and 1:1.5, respectively. The principal components in the EO were lupeol acetate, epiputranjivol, α-linoleic acid, hexadecanoic acid, and spathulenol. Interestingly, some new compounds were identified, such as globulol, betulinic aldehyde, ionone, and γ-sitosterol which had not previously been reported in S. rebaudiana EO. In addition, FT-IR analysis showed a greater abundance of alkynes, aldehydes, alkene, and alkanes were present in the EO. Furthermore, S. rebaudiana EO presented an interesting radical scavenging activity (RSA) against 1,1-diphenyl-2-picryl hydrazyl (DPPH) with IC50 values of 0.91± 0.25 μg/mL. Results obtained indicated the efficiency of SC-CO2 employed for extracting S. rebaudiana essential oil, which could be a good source of natural antioxidant and may be beneficial as a functional biomaterial with possible applications in food and pharmaceutical which can be used to cure the NCDs.